Singapore, Incorporated Versus the Private Sector : Are Government-Linked Companies Different? - Tan, Ling (IMF Working Papers; Working Paper ;, 2003)
Government-linked companies (GLCs) have a significant presence in Singapore's corporate sector. Unlike parastatals in many other countries, these companies are run on a competitive, commercial basis, ostensibly without government privileges. Based on data from publicly listed GLCs and non-GLCs, we indeed find no evidence that GLCs have easier access to credit. However, we do find that being a GLC is rewarded in financial markets with a positive premium, over and above what can be explained by the usual determinants of Tobin's q.